(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Goods and Service Tax (GST) is a comprehensive tax charge on manufactured goods, sale and utilization of products and enterprises. The essential thing in GST is to make uniform the scattered indirect tax system in India and evade the falling impact in tax assessment. It can be looked as simplification of Taxes in nation and staying away from pointless complexities. India is an elected nation which has different Tax management and structure, where Tax is demanded by the two Governments. After the execution of GST all the Indirect Taxes will be subsumed under an umbrella, it will be a turning point in the historical backdrop of Indirect Tax change. In this paper, an endeavour has been made to look at the real highlights of GST. This paper analyses structural faults in Indian GST.